Quantitative trait loci (QTL) and genetic parameters for economically important traits in chicken – A review - Goraga, Zemelak Sahle (Journal of Scientific Agriculture, 2019)
The study was aimed at reviewing and summarization of previous findings on associated genomic loci and estimated genetic parameters for reproductive traits in chicken. It was approached by reviewing various journals, books, genome database and used various genome browsing tools to collect the required information. Most of the reviewed information sources indicated that reproductive traits in chicken are genetically correlated, have low heritability and are affected by several quantitative trait loci (QTLs) that are located either on the same or different chromosomes. Both autosomal and sex chromosomes had influence on those traits. The majority of the reviewed QTLs had big confidence intervals and carries several candidate genes for the studied traits. Fine mapping using advanced intercross lines can help to narrow down the confidence intervals and target major genes. The information provided in this article, can contribute to our understanding of the complex inheritance pattern of the traits underlying reproductive performance in chicken.